Adaptations to Holiday Club Food Provision to Alleviate Food Insecurity During the Covid-19 Pandemic - Bayes, Natasha; Holley, Clare E.; Haycraft, Emma; Mason, Carolynne (Frontiers in Public Health, 2021)
Holiday clubs play a pivotal role in providing food and vital enrichment opportunities to alleviate food insecurity among children during the school holidays (holiday hunger). The need for these opportunities increased substantially for families throughout 2020, as food insecurity quadrupled in the UK during the Covid-19 pandemic. In this qualitative study, UK holiday club staff reflected on the adaptations they implemented in order to maintain food supplies and enrichment activities for families during the first UK national Covid-19 lockdown and subsequently throughout the summer of 2020. Staff also reflected on the opportunities and challenges related to implementing these adaptations during this period. Twenty-five holiday club staff engaged in video-based interviews during August and September 2020. The findings revealed a range of innovative changes to holiday club food provision, and the challenges and opportunities faced varied across holiday clubs. Challenges during the pandemic in some clubs included staff shortages (typically due to furloughing and/or increased working demands) and difficulties sourcing adequate funding. However, staff identified that the opportunities for holiday clubs included enhanced partnership working during the pandemic, increased engagement with digital technology to communicate with families and deliver online cooking sessions, and their ability to continue providing food and much needed enrichment opportunities for children unable to attend school and/or the holiday club. The ability of clubs to adapt their models of working when faced with adversity was essential in protecting their organisational resilience and delivering their vital services. The findings emphasise the important role that holiday clubs play in their communities and highlight their willingness to adapt and expand their role in response to the pandemic to continue to tackle food insecurity and provide vital food and enrichment opportunities to families. The findings also identify lessons that can be applied to practice in the future.